2019
DOI: 10.15414/raae.2019.22.02.03-09
|View full text |Cite
|
Sign up to set email alerts
|

Econometrics of Environmental Valuation: The Bayesian Inferences on Willingness to Pay Estimations

Abstract: This study applied the Bayesian approach to estimate people's willingness to pay (WTP) for mitigation of environmental hazards in oil producing areas in Nigeria. The Bayesian approach enabled estimation of the mixed logit model employing the normal and log-normal distributions of WTP parameters. The model estimate indicating a negative WTP values for the status quo (STAQUO) attribute suggests that people in oil producing areas in Nigeria do not like the current welfare situation and environmental condition whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…To address these negativities, Idemudia (2014), emphasised the need for improved corporate social responsibilities among multinational oil companies towards poverty reduction and development of oil producing rural communities in Nigeria. Also, Ukpong (2019), identified poverty as one of the major effects of oil and gas operations in oil producing areas, and suggested that appropriate mitigation measures be taken with reference to environmental laws and global best drilling practices.…”
Section: Introductionmentioning
confidence: 99%
“…To address these negativities, Idemudia (2014), emphasised the need for improved corporate social responsibilities among multinational oil companies towards poverty reduction and development of oil producing rural communities in Nigeria. Also, Ukpong (2019), identified poverty as one of the major effects of oil and gas operations in oil producing areas, and suggested that appropriate mitigation measures be taken with reference to environmental laws and global best drilling practices.…”
Section: Introductionmentioning
confidence: 99%